Sustainable urban development on the example of the housing deveopment of Zielona Góra (Poland), as a response to the climate policy of the European Union - Bazan-Krzywoszańska, Anna; Mrówczyńska, Maria; Skiba, Marta; Sztubecka, Małgorzata (International Conference “Environmental Engineering”, 2017)
In the world, in Europe, and also in Poland the use of energy is growing rapidly, causing concern about the difficulty of supply, a depletion of non-renewable energy resources and the increase in negative impacts on the environment (ozone depletion, global warming, climate change, etc. caused by increased emissions of CO2) (Balaras et al. 2005). Political or economic attempts to enforce climate change, through the increase in the price of fossil fuels, lead to exclusion and growth of energy poverty therefore they cause social effects (fossil fuels become so expensive that a large part of the population cannot afford their combustion). The ideal solution would be a combination of activities aimed at the energy modernization of cities with sustainable strategies of their rebuilding. The purpose of the article is a search for the optimal way of spatial policies at the local level that enable implementation of the objectives of the energy policy of the European Union. Factors affecting changes in the pollutant emissions associated with the combustion of fossil fuels, depending on the energy efficiency of selected buildings were modelled with a use of deduction based on radial neural networks. The observations presented in this article may be relevant for other regions that are interested in reducing polutant emission and energy consumption of buildings, housing estates and cities. Taking the geographical context into account, it is especially important for those regions which benefit from financial support of the European Union.